Ancient Siddha Approach Towards Mother and Child Health Care - Arthi, G; Lakshmana , kumar V; Sushil , Kumar P N; Rathinam , J (International Research Journal of Ayurveda & Yoga, 2022)
Siddha System of medicine is the ancient traditional system. The word Siddha means accomplished or perfect.‘ The food itself is medicine and medicine itself is food’ is one of the basic principles of the Siddha system of Medicine. Siddha Medicine not only acts as a curative and also as a preventive measure. Ancient Siddhars’ (Founders of the Siddha system) described Mother care includes Antenatal, Postnatal, and also child care. The Tamil Nadu Government introduced the ‘Amma Magaperu Sanjeevi Scheme’ for antenatal and postnatal care. During pregnancy we have to take care of a mother, she gets stressed and fears due to various factors such as hormonal changes in the body, increase in body weight, etc. So Siddha system helps to prevent miscarriage and facilitates normal vaginal delivery. In Kuzhanthai Maruthuvam (Siddha Pediatric) Siddha’s traditional formulation Urai Mathirai(Tablet) is advised for infants and children. This article briefly describes the ancient Siddha approaches to improving mother and child health care.